1999
DOI: 10.1080/00016489950180892
|View full text |Cite
|
Sign up to set email alerts
|

Speech Articulation after Subtotal Glossectomy and Reconstruction with a Myocutaneous Flap

Abstract: Speech samples of 9 subjects (8 males, 1 female) were recorded before and 0.5-2 years after a partial glossectomy and reconstruction with a pectoralis major myocutaneous flap. A reading sample, a list of meaningful and nonsense words, and a list of sustained vowels were recorded. The speech samples were evaluated by pairs of naive listeners and using acoustic analysis of the vowel production. Each pair listened to the recordings of only one patient. Inter-rater agreement was satisfactory. The general impressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Both formant values are altered by the surgical procedure. The utilization of an F1-F2 chart has evidenced modifications after glossectomy and mandibulectomy, as well as formant shift on the vowels average frequency 18,19 . In the literature, several authors have reported changes in formant values as a consequence of more or less extensive resections of the tongue [13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both formant values are altered by the surgical procedure. The utilization of an F1-F2 chart has evidenced modifications after glossectomy and mandibulectomy, as well as formant shift on the vowels average frequency 18,19 . In the literature, several authors have reported changes in formant values as a consequence of more or less extensive resections of the tongue [13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of an F1-F2 chart has evidenced modifications after glossectomy and mandibulectomy, as well as formant shift on the vowels average frequency 18,19 . In the literature, several authors have reported changes in formant values as a consequence of more or less extensive resections of the tongue [13][14][15][16][17][18][19][20] . On the other hand, speech intelligibility alterations are present in various neurodegenerative diseases in which the involvement of the lingual musculature results in an alteration of the articulatory dynamics and consequently in a modification of the phonatory joint, resonance and chewing [21][22][23][24][25][26][27][28] .…”
Section: Introductionmentioning
confidence: 99%